Simultaneous topology optimization of supporting structure and loci of isolators in an active vibration isolation system. (1st January 2018) - Zhou, Pingzhang; Du, Jianbin; Lü, Zhenhua
Highlights: Simultaneous topology optimization of supporting structure and loci of isolators is presented. A novel efficient topology optimization model for layout design of loci of isolators is proposed. Multi-level optimization strategy is proposed to consider the interactions between different design stages. Superiority of the proposed model and solution method is demonstrated by numerical examples. Abstract: We developed a new multi-objective and multi-level optimization method to design an active vibration isolation system. Both the layout of the continuum (i.e. the supporting structure) and the loci of the isolators are designed using topology optimization technique in a unified formulation for the first time. The static, dynamic and vibration-isolation characteristics are taken into account simultaneously in the present model. Due to their different roles in the system it may be appropriate and advantageous to treat the design of the continuum layout and isolator loci as different sub-problems with different objectives in separate stages. The multi-level optimization technique, where the optimization of the supporting structure and the isolator loci are incorporated into a closed-loop, is proposed and implemented so that the interactions between these two sub-problems can be fully taken into account. Numerical results demonstrate the validity of the proposed design cycle. Comparisons show that the overall static, dynamic and vibration-isolation performance of the optimized system outperforms the ones designed by traditional methods.